Asymmetric meso-CF3-BODIPY dyes based on cycloalkanopyrroles. (May 2020) - Tomilin, Denis N.; Sagitova, Elena F.; Petrushenko, Konstantin B.; Sobenina, Lyubov N.; Ushakov, Igor A.; Yang, Guoqiang; Hu, Rui; Trofimov, Boris A.
Abstract: New meso -CF3 -substituted BODIPY derivatives have been synthesized using the methodology that includes as a key step the condensation of pyrroles with trifluoro(2, 3-cycloalkanopyrrol-2-yl)ethanols. The further reaction of dipyrromethanes thus obtained with DDQ followed by complexation with BF3 leads to either benzo[ b ]-fused (in the case of dipyrromethanes obtained from trifluoro(4, 5, 6, 7-tetrahydroindol-2-yl)ethanol) or cycloheptano[ b ]-fused saturated or partially saturated BODIPY dyes. The latter exhibit strong red fluorescence (λem = 588–634 nm, Φf = 0.54–0.68), while benzo[ b ]-fused do not fluoresce at all in either polar or non-polar solvents. The performed quantum-chemical calculations (TD-CAM-B3LYP/SVP) explain the spectroscopic results. Graphical abstract: Image 1 Highlights: Complexation of asymmetric cyclohexano[ b ]-fused dipyrromethanes to BODIPY is accompanied by exhaustive aromatization. Cycloheptano[ b ]-fused dipyrromethanes are transformed to BODIPY dyes with partial dehydrogenation. Lack of fluorescence of indole[ b ]-fused BODIPY is explained by competition of the 1LE and 1CT states.